The Inhibitory Effect of Kakkonto, Japanese Traditional (Kampo) Medicine, on Brain Penetration of Oseltamivir Carboxylate in Mice with Reduced Blood-Brain Barrier Function. (19th February 2015) - Ohara, Kousuke; Oshima, Shinji; Fukuda, Nanami; Ochiai, Yumiko; Maruyama, Ayumi; Kanamuro, Aki; Negishi, Akio; Honma, Seiichi; Ohshima, Shigeru; Akimoto, Masayuki; Takenaka, Shingo; Kobayashi, Daisuke
Abstract : Oseltamivir phosphate (OP) is used to treat influenza virus infections. However, its use may result in central nervous system (CNS) adverse effects. In Japan, OP is used with Kampo formulations to improve clinical effectiveness. We evaluated the potential for using Kampo formulations to reduce CNS adverse effects by quantifying the CNS distribution of oseltamivir and its active metabolite oseltamivir carboxylate (OC) when administered with maoto and kakkonto. We administered lipopolysaccharide (LPS) by intraperitoneal injection to C57BL/6 mice to reduce blood-brain barrier function. Saline, maoto, and kakkonto were administered orally at the same time as LPS. OP was orally administered 4 hours after the last LPS injection and the migration of oseltamivir and OC was examined. Additionally, we examined the brain distribution of OC following intravenous administration. Changes in OC concentrations in the brain suggest that, in comparison to LPS-treated control mice, both Kampo formulations increased plasma levels of OC, thereby enhancing its therapeutic effect. Additionally, our findings suggest kakkonto may not only improve the therapeutic effect of oseltamivir but also reduce the risk of CNS-based adverse effects. Considering these findings, it should be noted that administration of kakkonto during periods of inflammation has led to increased OAT3 expression.